Has cutting become cool? : Normalising, social influence and socially-motivated deliberate self-harm in adolescent girls : a research project presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Albany, New Zealan - James, Shelley Anika (Massey University, 2013)
The literature focusing on deliberate self-harm (DSH) has grown exponentially over the last decade. The most commonly understood reasons for DSH are based on distress relief and attenuation of emotional numbness. However, few studies have explored the social aspects of DSH. With the advent of some youth subcultures where DSH appears to be routine, the possibility arises that DSH may have become a normalised, social behaviour which is influenced by peers and which may not always be rooted in underlying psychopathology, such as borderline personality disorder (BPD), or it may derive from a somewhat different pattern of underlying psychopathology than that which is usually found among those who engage in DSH. This study aimed to explore the differences between self-harming and non-self-harming adolescent girls, and between girls who self-harm for social reasons and those who endorse other reasons for DSH, in terms of social influence, underlying psychopathology and normalising of DSH. Participants were 387 adolescent girls (303 non-self-harmers and 84 self-harmers) from schools in the greater Auckland area. Results showed that socially-motivated selfharmers were more susceptible to peer pressure and endorsed higher levels of normalisation of DSH than their counterparts, although overall levels of normalisation were low. However, those who endorsed social reasons for harm did not do so exclusively and were just as likely to endorse emotional reasons. Social harmers did not differ from other harmers in terms of psychological problems but indicated that the impact of their problems was less. When compared to non-self-harmers, the selfharming girls scored higher in peer influence and lower in parent influence, and also scored higher on measures of psychopathology. Clinical implications and suggestions for further research are discussed.
Keywords: Self-harm; Adolescent girls; Teenage girls; Psychopathology